Fundamentals of Entrepreneurship (ENT 300) : Apparel Business / Patrick Sullang Ambun ... [et al.] - Ambun, Patrick Sullang; Jai, Azwan; Claisdell Lorren, Jeff Collven (2017)
Apparel business is the selected business due to lots of positive impacts over negative factors. The store. or also knowll as apparel business, is a retail business company that sells various of fitness apparel in terms of trendy. in demand and competitively priced, The store additionally sells others good equipment for selected sports. With supporting details. emphasis placed on high-growth products that has driven by current social trends, for example, exercise or fitness equipment, football, running, and fashion sports apparel as well.